In vivo immunotoxicity of Gd2O3:Eu3+ nanoparticles and the associated molecular mechanism. Issue 11 (13th July 2020) - Zheng, Cunjing; Tian, Xiumei; Cai, Jing; Huang, Long; Wang, Shunxin; Yang, Fanwen; Ma, Yanping; Xie, Fukang; Li, Li
Abstract: The in vivo toxicity of Gd2 O3 :Eu 3+ nanoparticles (NPs) used as dual‐modal nanoprobes for molecular imaging has not been studied, and the corresponding molecular mechanism of immunotoxicity remains unknown. In this study, we investigated the cytotoxicity, in vitro apoptosis, and in vivo immunotoxicity of Gd2 O3 :Eu 3+ NPs. The NPs showed little immunotoxicity to BALB/c mice. We explored the possible role of the phosphoinositide 3‐kinase (PI3K) signaling pathway and found that reactive oxygen species could act as secondary messengers in cellular signaling, inhibiting PI3K expression in the liver. The immune suppression caused by PI3K inhibition helped the mice adapt to stress. The immunotoxicities caused by Gd2 O3 :Eu 3+ and gadodiamide, a commonly used contrast agent, were not significantly different, and the mice were able to tolerate the immunotoxicity caused Gd2 O3 :Eu 3+ NPs in vitro and in vivo experiments. The results suggest that Gd2 O3 :Eu 3+ NPs are sufficiently biocompatible to be used safely in preclinical applications and show promise as bio‐imaging agents. Moreover, the in vivo molecular mechanism of immunotoxicity caused by the Gd2 O3 :Eu 3+ NPs provides a platform for further research on the immunotoxicity of nano‐sized biomaterials.